Moringa Oleifera Leaf Consumption On The Vitamin A And Haematological Status Of School Children In Ada-East District, Ghana - Glover-Amengor, M.; Aryeetey, R.; Owusu, W.B.; et al. (Int. J. Food, Nutrition and Public Health, 2017)
Background: Vitamin A deficiency (VAD) could be prevented by the consumption of pro-vitamin A (β-carotene)-rich Moringa oleifera (M. oleifera) leaves. M. oleifera grows well in many developing countries and dried leaves also retain a high percentage of β-carotene in storage; they could thus serve as an excellent, convenient source of this pro-vitamin A carotenoid. This study assessed the efficacy of the supplementation of dried M. oleifera leaves on the vitamin A and haematological status of children in Ada-East district, Ghana. Methodology: Children aged 5–12 years were supplemented thrice a week at 0.2 g/kg body weight for nine weeks. Background data were collected on the socio-demographic status of the children. Data were collected on the children's vitamin A and haematological status at baseline and at the end of the study. Malaria and hookworm morbidity were also assessed at baseline and the end of the study. Results: There was a significant increase in mean serum vitamin A levels after supplementation (end of study) in the intervention group (p,0.05), but not in the control group. Haematological parameters Haemoglobin (HGB), Red Blood Count (RBC), Haematocrit (HCT), and Mean Corpuscular Volume (MCV) did not show any significant changes in either group (p,0.05). A bivariate analysis, however, showed a significant association between vitamin A and haematological indices in the intervention group, but not in the control group. Conclusion: M. oleifera leaf consumption significantly increased the vitamin A status of children in Ada-East district, Ghana, has the potential to increase children's haematological status. It could thus play a major role as a food-based strategy in vitamin A deficiency control.
Research Article
Keywords: Moringa oleifera leaves; Vitamin A deficiency; Intervention; β-carotene; Ghana; Vitamin A status